VALUE RATIONALITY OF PEOPLE LIVING ON THE SLOPE OF MERAPI IN YOGYAKARTA - Napsiah, Napsiah; Gunawan, Budhi; Abdoellah, Oekan Soekotjo; Sulaeman, Munandar (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
This study aims to describe rationality of the people who live in the eruptionprone areas of Mount Merapi and who refuse to be relocated. A qualitative research method with interpretative phenomenological analysis is used in this research. Informants are selected by snowball sampling technique. The location of research is in Pangukrejo village which is a village in the southern slopes of Merapi. The results show that people think Merapi as a place of origin where they obtain senses of comfort and safety. Merapi is also a place where they acquire and preserve community value system. Merapi is a symbol of their dignity that must be maintained. In this relation, eruption is interpreted as destiny, eruption is interpreted as destiny of God that can not be circumvented. At that time, their living conditions were on the bottom and could be overcome by means of mutual cooperation to return to normal condition. The value rationality motivate them to resettle in their homes after the great eruption of Merapi.